Efeito da suplementação de selenometionina e vitamina C sobre as características do sêmen de coelho - Alvarez, Cristiane Arieta (2005)
: The work was carry out to analise the effects of the selenomethionine, vitamin C and the combination of selenomethionine and vitamin C on semen characteristics in New Zealand White rabbits with six months of age. Were used 125 rabbits male, kept individually in cage and distributed in completely randomized design with twenty five treatments (vitamin C and selenomethionine added in the diets) and five replications. Semen was collected once a week, during eight weeks, totalizing eight collects by animal. The evaluated parameters were: volume, color, pH, progressive motility, spermatic vigor, and spermatic concentration/mm3 and, spermatic morphopathologies: NO - normal; PT - total pathologies; PP - primary pathologies; PS - secondary pathologies; CD - bent tail; CAB - abaxial tail; CABI - forked tail; CAPE - pyriform head; CAPS - free cap; CARE - raquetiform head; CASO - tailess; CAUSO - headless; CDE - degenerate tail; CDF - final bent tail; CEN - coiled tail; CENF - final coiled tail; CQF - final broken tail; CQI - initial broken tail; CQIN - mid-piece broken tail; CQJC - tail broken close head; EDCO - swollen neck; GODI - distal droplet; GOPR - proximal droplet; MACRO - sperm macrocephalic; MICRO - sperm microcephalic. There was a significant difference to the treatments with VC (P <0.05) considering the color and spermatic concentration. Volume with and without gelatin, pH, progressive motility and spermatic vigor didn't show significant differences (P>0.05) among the treatments. There wasn't interaction between the selenomethionine and vitamin C in the treatments, not influencing semen characteristics. The ration intake increased lineally according to the increasing of vitamin C levels in the treatments, but there wasn't any effect of selenomethionine levels. Considering the spermatic morphology the following parameters were influenced by treatments of SeM and VC (P<0.05): PT, PP, PS, CD, CAB, CAPS, CARE, CAUSO, CENF, GODI, GOPR, MICRO, but the others were not influenced (P>0.05) by the same treatments. The treatments with SeM and VC increased the parameters until on intermediate level, reducing them later: PT, PP, CD, CAB, CARE, CAUSO and GODI. The GOPR was reduced until the intermediate levels of 300 mg SeM/kg of ration, showing the efficiency of the selenium in the spermatozoa maturation. The sperm microcephalic parameter presented a positive linear effect relationed to the vitamin C, decreasing the sperm microcephalic number as there was the vitamin C increased, showing the effect of antioxidant protection in the spermatozoa. As conclusion it was observed that some quantitative and qualitative parameters (color and spermatic concentration) and some morphopathologies (MICRO and CAUSO) improved with the inclusion of, vitamin C.